2021
DOI: 10.1101/2021.06.19.21259165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Health-Related Quality of Life in Patients With Diabetes in Different Care Settings a Cross Sectional Study in Alain, Uae

Abstract: Purpose This study aims to assess health related quality of life (HRQOL) in type 2 diabetic patients across four domains physical psychological social and environmental and explore the possible determinants of these domains. Methods Using a cross sectional study design 397 type 2 diabetic patients in Alain city were interviewed using validated questionnaires in three different care settings: primary secondary and private health care facilities. The WHO Quality of Life instrument generalized anxiety disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Through the results shown in Tables (2) and (3), the following hypothesis can be rejected: There is no effect and role of moral significance that confirming the commitment and responsibility of the external auditor in control and auditing and stating the neutral professional and technical opinion towards quality costs in industrial companies will contribute to rationalizing administrative decisions and achieving product quality and performance in those companies.…”
Section: Table 3 the Estimated Values Of The Coefficient Of The Simpl...mentioning
confidence: 99%
“…Through the results shown in Tables (2) and (3), the following hypothesis can be rejected: There is no effect and role of moral significance that confirming the commitment and responsibility of the external auditor in control and auditing and stating the neutral professional and technical opinion towards quality costs in industrial companies will contribute to rationalizing administrative decisions and achieving product quality and performance in those companies.…”
Section: Table 3 the Estimated Values Of The Coefficient Of The Simpl...mentioning
confidence: 99%
“…The fuzzy rules were designed and applied for the assignment of Resource Units (RU) to a certain job. Al-Kaabi M et al [76] presented a Multi-Objective Slime Mould Algorithm (MOSMS), which fuzzy set theory was used to obtain the optimal solution. Yutong G et al [77] present a fuzzy SMA(named as FSMA) whose control parameters was updated by a fuzzy system.…”
Section: Fuzzymentioning
confidence: 99%
“…Yin S et al [73] applied the proposed multi-objective EOSMA (MOEOSMA) for the inverse kinematics of manipulators. Al-Kaabi M et al [76] presented a MOSMA for attacking multi-objective optimal power flow problems. Luo Qifang et al [80] proposed a MOEOSMA and assessed it in engineering problems, which indicated its efficiency from comparison.…”
Section: Multi-objective Version Of Smamentioning
confidence: 99%
See 1 more Smart Citation